2015
DOI: 10.1530/rep-15-0155
|View full text |Cite
|
Sign up to set email alerts
|

Incubation history prior to the canonical thermosensitive period determines sex in the American alligator

Abstract: Despite the widespread occurrence of environmental sex determination (ESD) among vertebrates, our knowledge of the temporal dynamics by which environmental factors act on this process remains limited. In many reptiles, incubation temperature determines sex during a discrete developmental window just prior to and coincident with the differentiation of the gonads. Yet, there is substantial variation in sex ratios among different clutches of eggs incubated at identical temperatures during this period. Here, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…We could not confirm sex histologically as both gonads of each embryo were used for RNA sequencing, so we confirmed the sex of each embryo by comparing gonadal expression of CYP19A1 to AMH as in previous studies McCoy et al 2015). One embryo from clutch 13 was female despite incubation at MPT (Fig.…”
Section: Sex-biased Gene Expressionmentioning
confidence: 75%
See 2 more Smart Citations
“…We could not confirm sex histologically as both gonads of each embryo were used for RNA sequencing, so we confirmed the sex of each embryo by comparing gonadal expression of CYP19A1 to AMH as in previous studies McCoy et al 2015). One embryo from clutch 13 was female despite incubation at MPT (Fig.…”
Section: Sex-biased Gene Expressionmentioning
confidence: 75%
“…Due to conditions prior to egg collection, embryos can sometimes develop as a different sex than expected based on incubation temperature after collection (McCoy et al 2015). We could not confirm sex histologically as both gonads of each embryo were used for RNA sequencing, so we confirmed the sex of each embryo by comparing gonadal expression of CYP19A1 to AMH as in previous studies McCoy et al 2015).…”
Section: Sex-biased Gene Expressionmentioning
confidence: 89%
See 1 more Smart Citation
“…In alligators specifically, egg incubation at 30°C (female-producing temperature) during the TSP produces 100% females, whereas egg incubation at 33.0-33.5°C (maleproducing temperature, MPT) during the TSP produces 100% males (Ferguson & Joanen, 1983;Lang & Andrews, 1994;McCoy, Parrott, Rainwater, Wilkinson, & Guillette, 2015). In alligators specifically, egg incubation at 30°C (female-producing temperature) during the TSP produces 100% females, whereas egg incubation at 33.0-33.5°C (maleproducing temperature, MPT) during the TSP produces 100% males (Ferguson & Joanen, 1983;Lang & Andrews, 1994;McCoy, Parrott, Rainwater, Wilkinson, & Guillette, 2015).…”
Section: American Alligator As a Model Of Endocrine Disruptionmentioning
confidence: 99%
“…However, Dr. Guillette’s laboratory showed that the process of TSD at the PVT can be heavily influenced by incubation temperatures earlier than the known temperature sensitive period (TSP) in A. mississippiensis (McCoy et al, 2015). Since much of the work on TSD has been conducted in the laboratory where egg-incubation temperatures do not fluctuate as they naturally do in the field (Georges et al, 2004), further investigations into this earlier TSP, temperature fluctuation, and the molecular mechanisms driving TSD are required in A. mississippiensis , as well as other TSD species.…”
Section: Contributions To Evolutionary Biologymentioning
confidence: 99%